(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Fermented shrimp-based products, primarily derived from Acetes spp., are globally consumed and play a crucial role in food quality and extending shelf stability. Fermentation establishes an environment that is unfavourable to spoilage microorganisms; however, natural fermentation stimulates the growth of different microorganisms derived from the shrimps or salts applied in the fermentation. Thus, the primary free amino acids and biogenic amines (BAs) were produced as a result of shrimp-based fermentation. This review aims to describe knowledge on biogenic amines, amino acids, and microbial diversity within fermented shrimp-based products, with a focus on those produced in Asia. Proteinases produced by fermenting microorganisms break down the proteins into smaller peptides and amino acids, and the microbial decarboxylation of amino acids causes the formation of biogenic amines (BAs), which pose health risks. Various analytical approaches have been studied, including high-performance liquid chromatography (HPLC) for quantifying amino acids and biogenic amines. The profiling of diversity and function of microbes present in a wide range of fermented shrimp-based products can be examined in detail using molecular and next-generation sequencing (NGS). Additionally, this review examines the functional contributions of these elements, addresses challenges, and proposes future research directions. Further research on fermented shrimp-based products is essential for advancing food science and promoting human health benefits.